2023
DOI: 10.1007/s15010-023-01978-0
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HPV vaccination among boys after the introduction of gender-neutral HPV vaccination in Germany before and during the COVID-19 pandemic

Abstract: Background HPV vaccination has been recommended and reimbursed for girls in Germany since 2007. In June 2018 the German Standing Committee on Vaccination (STIKO) recommended the gender-neutral vaccination of adolescents aged 9 to 14 years with catch-up through age 17. Objectives of this study were to describe the uptake of vaccination in boys before and during the COVID-19 pandemic. Methods The study used data from a proprietary electronic medical record d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…The KIGGS Wave 2 follow-up study after 5 years showed a stable HPV vaccination coverage among German girls [ 18 ]. A study that examined boys in Germany after the STIKOs HPV vaccination recommendation in 2018 showed that the initial HPV vaccination rates of boys were comparable in the first months of the recommendation to those of girls, but declined steadily from year to year – presumably due to the Corona pandemic [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KIGGS Wave 2 follow-up study after 5 years showed a stable HPV vaccination coverage among German girls [ 18 ]. A study that examined boys in Germany after the STIKOs HPV vaccination recommendation in 2018 showed that the initial HPV vaccination rates of boys were comparable in the first months of the recommendation to those of girls, but declined steadily from year to year – presumably due to the Corona pandemic [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Als Beispiel für eine zunehmend erfolgreiche Kampagne nennen wir den Anstieg der HPV-Impfquote. Seit 2007 ist die Impfung in Deutschland verfügbar und wird seit 2018 auch Jungen empfohlen, jedoch lag die Impfquote 2019 bei Mädchen unter 50 % und bei Jungen bei knapp 5 % [2].…”
Section: Impfungenunclassified
“…Die Immunogenität soll durch die in vitro aktivierten zytotoxischen CD 8 + T-Zellen, die das Tumorgewebe erkennen und infiltrieren, verbessert ▶Abb. 1 Anstieg der HPV-Impfungen bei Jungen (nach [2]). werden.…”
Section: Geeignete Beispiele Für Die Präzisionstherapie Aus Der Onkol...unclassified
“…Bundesweit hatten 2020 17,0 % und 2021 26,5 % der 15-jährigen Jungen eine vollständige HPV-Impfserie erhalten [74]. Wie auch für andere Impfungen, hat die COVID-19-Pandemie zu einer Reduktion der verimpften HPV-Dosen sowohl bei Mädchen als auch bei Jungen geführt [75]. Im Vergleich der HPV-Impfraten in Europa nimmt Deutschland einen Platz im unteren Drittel ein (Rang 17 von 25).…”
Section: Impfempfehlungen Und Impfraten In Deutschlandunclassified